1999
DOI: 10.1063/1.369106
|View full text |Cite
|
Sign up to set email alerts
|

Noise analysis of a 1 MHz–3 GHz magnetic thin film permeance meter

Abstract: We analyzed the permeability measurement error of a low permeance thin film. We clarified that the noise voltage was excited by a current loop which is composed of the coaxial cable and the ground plane. The current loop should be removed for high sensitivity of the permeameter. The permeability of a high electrical resistivity film (CoFeHfO) has been demonstrated 1 MHz–3.5 GHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…The hard-axis magnetic permeability was measured by a custom-built permeameter with a frequency range up to 3 GHz on samples with an area of 5 × 5 mm 2 . The details of the permeameter are available in reference [11]. The resistivities of these FeCoN films were measured with a four-point probe station.…”
Section: Methodsmentioning
confidence: 99%
“…The hard-axis magnetic permeability was measured by a custom-built permeameter with a frequency range up to 3 GHz on samples with an area of 5 × 5 mm 2 . The details of the permeameter are available in reference [11]. The resistivities of these FeCoN films were measured with a four-point probe station.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the structure of a Co-Fe-Hf-O film consisted of α-Fe(Co)-rich bcc nanograins embedded in a HfO 2 -rich amorphous matrix [10,17,19]. The highly resistive HfO 2 -rich amorphous matrix contributed to the high resistivity of the film which significantly suppressed eddy current loss, and consequently gave rise to the good highfrequency performance [10][11][12][13][14][15][16][17]. The addition of large amounts of Hf and O was found to significantly increase the electrical resistivity of Co-Fe-Hf-O films but, in turn, deteriorate their magnetic softness [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Hayakawa et al [10] first reported that Fe-M-O (M = Hf, Zr) magnetic films possessed a good magnetic softness owing to their nanostructure which consisted of ferromagnetic bcc nanocrystals (∼10 nm in size) embedded in an amorphous matrix containing large amounts of M and O elements. Soon after this work, several attempts were made to improve the high-frequency performance of these films [11][12][13][14][15][16][17][18][19]. It was found that the addition of Co to Fe-Hf-O films led to a significant improvement in the high-frequency magnetic response, mainly due to an increase in the crystalline anisotropy of the nanograins.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations